Evaluation of the anti-cancer potential of Nigella sativa and its bioactive constituents thymoquinone and alpha-hederin - Zafar, Mashal (2024)
The exploration of natural compounds with potential anti-cancer properties has gained significant attention in recent years. Nigella sativa (NS), commonly known as black seed, has emerged as a promising candidate due to its rich composition of bioactive constituents. Thymoquinone (TQ) and alpha-hederin (aH), the bioactive constituents of NS seeds, effectively inhibit tumour cell progression through diverse molecular mechanisms but their progression to clinical trials, like most plant derived therapeutic compounds, is confronted with two major challenges, their low bioavailability and toxicity at higher concentrations. The work herein began by investigating the anti-cancer activities of TQ and aH individually against cell lines of oesophageal, oral, breast and ovarian origin, specifically OE-19, H357, MCF-7, SK-OV-3 and MCF10A cells, each characterized by unique genetic and environmental factors. Both TQ and aH were shown to inhibit the proliferation, migration and cell viability in each cell line. To address the limitation of toxicity of TQ and aH, the effects of combination of both compounds at different percent concentrations were investigated in OE-19, H357, MCF-7 and SK-OV-3 cells where they demonstrated a high synergy in MCF-7 and SK-OV-3 cells, a moderate synergy in OE-19 cells and an antagonistic effect in H357 cells. Consequently, to address the second limitation regarding their low bioavailability a copolymer methyl ether-block-poly (lactide-co-glycolid-poly(ethylene glycol) (PLGA-PEG) nanoparticle (NP) vehicle for TQ, with further sodium dodecyl sulphate (SDS) modification (SDSNP0TQ) were developed (NP-TQ) which can improve the therapeutic index of a drug by readily penetrating biological membranes through their reduced particle size (79.30 ± 52 nm). Treatment of cells with NP-TQ and SDSNP-TQ significantly enhanced the antiproliferative activity of free TQ in each cell line by reducing the particle size, making TQ and aH more bioavailable to cancer cells.